Interference Patterns. Optical vs Tactile Experiments of Spatial Inmersion, from Psychogeography to Holograms - Antón, Javier; Lauter, Max; Reina, Teresa (Espacio Tiempo y Forma. Serie VII, Historia del Arte, 2021)
The impetus of this project is to gain a historical perspective on some conflicting philosophical theories on perception and representation of space, and to trace a démodé method of representation, that has remained in use in some contexts. The research focuses on the tension between two sensory experiences: tactility and opticality. It is an interweaving of critical narratives to examine ways of perceiving space in the context of artistic and architectural practices. Departing from the optical understanding of space and materialized in some examples such as El Lissitzky’s «Proun Room», Yves Klein’s «The Void» and Lebbeus Woods’ tectonic visuality; this article focuses on the tactile spatial perception theories of the ‘Situationists’ and ‘Surrealists’, with their dérivé mapping techniques, their mediated history/memory of urban space and their approach to capitalism and systems of control. All of this is finally interpreted through the lens of the optical practice of holography, and its success (and failure) as a representational tool.